Research on Physical and Psychological Activities of Sports Players in Association with Primary Angle Glaucoma - Ayhan ÖNAL , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
People with primary angle glaucoma should be cautious about the physical activities they engage in, as these activities might lead to a rise in intraocular pressure. Hence, improvements in healthcare sectors have assisted in dispelling these myths. Yet, due to increased competition, those with primary angle glaucoma are more prone to experience psychological anguish. This research aims to investigate the effect of mental and physical activities on the psychological stress of athletes with primary angle glaucoma. For this reason, an experimental study was done, and around 115 athletes from diverse Iraqi public high schools were chosen. They were divided into four groups: control, physical, psychological, and combined activities. This study was done over 12 weeks, and the "Psychological Stress Scale" was utilized to measure psychological stress for all groups. The statistical analysis was conducted using SPSS. After 12 weeks of experimental treatment, both psychological and physical groups had a significant impact on various dimensions of psychological stress, including development (p= 0.012), social contact (p= 0.015), and life (p= 0.031) (p ˂0.05), total scores (p= 0.001), life events (p= 0.002), and family (p= 0.0001) (p ˂0.01). The physical exercises were kept at a moderate to low intensity to prevent exertion on the volunteers. This study concludes that combining physical and psychological activities is essential for lowering psychological stress in players with primary angle glaucoma.